Paying more to wait less: Estimating the cost of reducing Ireland's public hospital waiting lists - Aoife Brick; Conor Keegan (The Economic and Social Research Institute (ESRI), 2020)
Larger and longer waiting lists for public hospital appointments and treatment have been a significant challenge in Irish healthcare for decades. The issue has been further exacerbated by COVID-19 in 2020 with the cancellation of elective activity in public hospitals for several months. The aim of this analysis is to estimate the activity and expenditure required to clear the accumulated backlog and account for future service demand. We estimate that to clear the backlog of cases and keep pace with demand over a period of five years, additional expenditure excluding any associated capital costs of up to exteuro1.1bn would be required.
Keywords: 330; acute hospitals; expenditure; waiting lists; waiting times